Odpowiedź:
t = 1,1 s
Wyjaśnienie:
h = 6 m (wysokość)
g = 9.8 [tex]\frac{m}{s^{2} }[/tex] ( przyspieszenie ziemskie )
Vo = 0 [tex]\frac{m}{s}[/tex] ( prędkość początkowa )
V - prędkość końcowa
Z zasady zachowania energii otrzymamy:
Ep = Ek
m * g * h = [tex]\frac{mV^{2} }{2}[/tex] /*2
2 * m * g * h = [tex]m * V^{2}[/tex] /:m
2 * g * h = [tex]V^{2}[/tex] /[tex]\sqrt{}[/tex]
V = [tex]\sqrt{2 * g * h}[/tex] = [tex]\sqrt{2 * 9,8 \frac{m}{s^{2} } *6 m } =[/tex] [tex]\sqrt{117,6 \frac{m^{2} }{s^{2} } } =[/tex] 10,84 [tex]\frac{m}{s}[/tex]
V = g * t /:g
[tex]t = \frac{V}{g} = \frac{10,84 \frac{m}{s} }{9,8 \frac{m}{s^{2} } }=[/tex] [tex]1,1 s[/tex]